2021
DOI: 10.3390/ijms22137041
|View full text |Cite
|
Sign up to set email alerts
|

Peptide/β-Peptoid Hybrids with Ultrashort PEG-Like Moieties: Effects on Hydrophobicity, Antibacterial Activity and Hemolytic Properties

Abstract: PEGylation of antimicrobial peptides as a shielding tool that increases stability toward proteolytic degradation typically leads to concomitant loss of activity, whereas incorporation of ultrashort PEG-like amino acids (sPEGs) remains essentially unexplored. Here, modification of a peptide/β-peptoid hybrid with sPEGs was examined with respect to influence on hydrophobicity, antibacterial activity and effect on viability of mammalian cells for a set of 18 oligomers. Intriguingly, the degree of sPEG modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…It was previously reported that the hemolytic activity and the hydrophobicity are easily predictable when the HPLC profiles are evaluated. They may be predicted by using the retention time and the % of acetonitrile, which may help to analyze the potential of different AMPs ( Frederiksen et al, 2021 ). One of the advantages of including fatty acids is the ease of permeation of molecules within human cells.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that the hemolytic activity and the hydrophobicity are easily predictable when the HPLC profiles are evaluated. They may be predicted by using the retention time and the % of acetonitrile, which may help to analyze the potential of different AMPs ( Frederiksen et al, 2021 ). One of the advantages of including fatty acids is the ease of permeation of molecules within human cells.…”
Section: Introductionmentioning
confidence: 99%